P69 An exploratory study to investigate the relationship between fraction of exhaled nitric oxide (FeNO) home monitoring and eosinophilic airway inflammation in adults with severe asthma. (12th November 2015) - Nanda, CR; Singapuri, A; Soares, M; Monteiro, W; Siddiqui, S; Gonem, S
Abstract : Introduction: FeNO is a non-invasive surrogate marker of corticosteroid-responsive airway inflammation that may be measured using small portable devices. We aimed to determine (i) the reliability and feasibility of twice-daily FeNO home monitoring in adults with severe asthma, as well as (ii) to explore the relationship between serial FeNO measurements and gold standard markers of eosinophilic airway inflammation. Methods: Ten patients with severe asthma (BTS treatment steps 4/5) were recruited from the Difficult Asthma Clinic at Glenfield Hospital. Patients were provided with portable FeNO monitors (NOBreath, Bedfont Scientific Ltd., Maidstone, UK) for a period of eight weeks, and asked to record twice-daily FeNO (at a flow rate of 50 ml/s) and PEF readings, as well as daily visual analogue scores for cough, breathlessness and wheeze, using paper diaries. They attended fortnightly visits during the study period, at which they underwent sputum induction and full blood count. Results: Nine patients completed the study. The median (range) intraclass correlation coefficient of triplicate FeNO measurements was 0.83 (0.78 – 0.92) for morning measurements and 0.82 (0.71 – 0.97) for evening measurements. There was a median of 7.1% missing data (range 2.7 – 14.3%). FeNO measurements correlated strongly with sputum and blood eosinophil counts, with the strongest correlations observed with a 9-day FeNO moving average, and a lag time of -1 day for sputum eosinophils (r = 0.571, p < 0.001) and -2 days for blood eosinophil counts (r = 0.691, p < 0.0001), suggesting that changes in sputum and blood eosinophil counts tended to precede changes in FeNO by 1 and 2 days respectively. In contrast there were no consistent relationships seen between FeNO and either PEF or visual analogue scores. Conclusion: Home monitoring of FeNO is feasible and the measurements are repeatable. Daily FeNO measurements correlate strongly with sputum and blood eosinophil counts, and are most useful when a moving average is taken over approximately 9 days. Further studies are required to determine if daily FeNO measurements may have a role in predicting loss of asthma control or exacerbations.